IPO or SBO?: The Increasing Importance of Operational Performance for Private Equity Exits Following the Global Financial Crisis of 2007–08. Issue 1 (6th April 2017) - Plagborg‐Møller, Emil; Holm, Morten
Abstract : The authors report the findings of their recent study of the role of portfolio company operating performance in determining the choice of exit options by private equity firms between initial public offerings (IPOs) and secondary buyouts (SBOs), and how that role may have changed since the Global Financial Crisis of 2007–2008. Virtually all studies of PE exits in all countries have found that portfolio companies that exit through IPOs tend to be larger and have higher operating returns than companies that exit through SBOs or sales to other companies. After examining the exits of PE portfolio companies based in Denmark and Sweden during the period 2003–2013, the authors report that, although general market conditions continue to be a major factor, operating performance and size have become even more important requirements for IPO exits since the crisis. And thus PE firms that fail to make operating improvements in their portfolio companies are likely to find their exit options limited.